Idiopathic sphenoid sinus CSF rhinorrhoea. (23rd April 2013) - Gupta, Manish; Gupta, Monica; Bindra, Gavinder; Singh, Sunder
Abstract : Cerebrospinal fluid (CSF) rhinorrhoea results from a direct communication between the CSF-containing subarachnoid space and the mucosa-lined space of the nasal cavity and paranasal sinuses. We present a case of 40-year-old woman, presenting with clear, watery discharge through the right nostril spontaneously. The CT cisternography confirmed the diagnosis of sphenoid sinus CSF rhinorrhoea, with no intracranial pathology. The patient was managed by transnasal endoscopic procedure, wherein bath plug technique was followed using temporalis fascia and overlay grafting with fascia lata and fibrin glue. The patient has been symptom free for the last year.